Athletic body in balance : optimal movement skills and condition for performance - Cook, Gray, ....- (Champaign : Human Kinetics, 2003)
Great athletes make difficult moves look effortless with a combination of skill, strength, and balance. Traditional conditioning builds a fitness base, but modern sports training takes into account athletic movement patterns. Athletic Body in Balance is the first guide of its kind to show you how to train for smooth, fluid movement and prevent muscle imbalances, mobility restrictions, stability problems, and injuries. Physical therapist and sports conditioning expert Gray Cook has proven the effectiveness of his approach through the performances of athletes in the NFL, NBA, NHL, WNBA, and Reebok[registered University's sports training system. Cook's methods will help you identify functional weaknesses; correct imbalances; explore your potential; and refine sport-specific movement skills such as jumping, kicking, cutting, and turning. You will see where conditioning is breaking down and how to get your body back on track. Whereas other books concentrate on maximizing your strengths, Athletic Body in Balance focuses on exposing and overcoming your weaknesses to form a foundation for long-term training gains. Learn how to maintain what you gain and build on your improvements. Make this comprehensive assessment tool your training guide. Prepare and repair your body for ultimate athletic performance with Athletic Body in Balance .